Monitoring the convection coefficient in fermentative processes using numerical methods - da Paz, Priscila Marques [UNESP]; de Oliveira, Juliana [UNESP] (Springer Nature, 2018)
This work is based on the importance of monitoring the thermodynamic variables of sugarcane juice fermentation by Saccharomyces cerevisiae, using a numerical technique, and providing artifices that lead to the best performance of this bioprocess. Different combinations of yeast quantity were added to diverse dilutions of cane juice, allowing the evaluation of the fermentation performance. This was conducted by observing the temperature signal obtained from thermal probes inserted in the experimental set up. The best performances are utilized in the mathematical model evaluation. Thus, the signal reconstructed by the appropriate inverse problem and subsequently, regularized by the simplified method of least squares (the method used for adjusting the defined parameters) allows a common method to process the convection coefficient that can be monitored and controlled within an actuation range. This leads to an increased level of refinement in the technique. Results show that it is possible to determine the best parameters for this technique and observe the occurrence of fermentation by monitoring the temperature signal, thereby ensuring the realization of a high-quality and high-performance bioprocess.
Keywords: Alcoholic fermentation; Convection coefficient; Inverse problem; Regularization; Temperature